STUDY PELAYANAN PUBLIK SURAT IZIN PERDAGANGAN (SIUP) DI KANTOR BADAN PELAYANAN TERPADU (BPT) DI KECAMATAN MANDAU KABUPATEN BENGKALIS - Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Increasingly important role permissions to be improved , especially in the era of development now and in the future . Development is carried out essentially intends to bring fundamental change and growth in the various sectors . But that development does not lead to the desired negative impacts that could harm , we need a control of the government through the licensing policy . The purpose of this study was : To determine the quality of service in the Office of Integrated Services licensing ( CPM ) Mandau sub Bengkalis . And to know what aspects that affect the quality of licensing services in the Office of Integrated Services Agency ( CPM ) Mandau sub Bengkalis . Thus it is known that Licensing Services In Integrated Services Office ( OPT ) Mandau sub Bengkalis (Studies in Licensing Services License) is considered good enough Keywords : Public Service , Business Licenses , Trade